(untitled) (Journal of Economic Research & Business Administration, 2016)
In article need of application of auditor service - accounting outsourcing, as opportunities to minimize accounting and tax risks at the enterprises of the Republic of Kazakhstan is considered. Also the author gives advantages and shortcomings of use of outsourcing services for the purpose of decrease in registration risks and achievement of a continuity of activity of the enterprise. The essence of accounting outsourcing consists that auditor firm, having signed the contract with the enterprise, assumes maintaining the bukhgalterksky account on it. outsourcing of accounting services is very demanded today among many companies as it is really favorable. It includes conducting accounting and tax accounting; optimization of tax payments and work with tax authorities; drawing up intermediate and annual otchetnost. Accounting outsourcing prevents risk of distortion of the reporting or the wrong reflection of accounting operations. In this regard the probability of wrong conducting accounting, calculation of tax payments decreases, so, the risk connected with the organization of accounting at the enterprise considerably decreases.